Microbial production of food ingredients and additives - Holban, Alina Maria; Grumezescu, Alexandru Mihai (Handbook of food bioengineering, 2017)
The latest release in the 'Handbook of Food Bioengineering' series, this is a solid resource on how microorganisms can increase food production and quality. Microorganisms are used to create and enhance food, used as food additives to improve food taste, and in improving function and fortification to benefit overall health. The book presents the applications of microbial products in food bioengineering and methods to obtain valuable ingredients, such as sugars, acids, secondary metabolites, enzymes and vitamins.